PENGARUH GRIT DAN GENDER DALAM PENGAMBILAN KEPUTUSAN KARIR MAHASISWA - Sovi Septania; Khairani Khairani (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2019)
Rapid development of technology and challenges in upcoming industrial revolution 4.0 require students to equip themselves with relevant competencies. The success of students as prospective workers will depend on this. Initial stage for students is to have clarity on the direction of career preparation. Adequate career preparation, including the accuracy of career decision making is synchronized between their potential versus what is desired (Sharf, 2002). Internal factorof students’ success in choosing a future career is by having strong characters. Character with perseverance and great desire to achieve long-term goals in a long time is known as grit ((Duckworth, Peterson, Matthews & Kelly, 2007). This study aims to identify the influence of grit and gender on career decision making among Psychology faculty’s students in UniversitasMuhammadiyah Lampung. The research involved 83 students from 4 classes and using quantitative research method using a scale as a data collection tool. Results of empirical research prove that grit and gender are proven to significantly influence students' career decision making. Grit correlate to career decision making with pearson-correlation score 0.519 (p <0.001) and gender correlate to career decision making with pearson-correlation score 0.277 (p <0.005). Simultaneously,  grit and gender make 28% (p<0.000) effective contribution to student’s career decision making. Further research is expected to be able to examine the interventions that can be done to improve the ability of taking career decisions for students.